2018
DOI: 10.1038/s41598-018-21579-4
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Stable, High Performance Transfer Doping of Diamond using Transition Metal Oxides

Abstract: We report on optimisation of the environmental stability and high temperature operation of surface transfer doping in hydrogen-terminated diamond using MoO3 and V2O5 surface acceptor layers. In-situ annealing of the hydrogenated diamond surface at 400 °C was found to be crucial to enhance long-term doping stability. High temperature sheet resistance measurements up to 300 °C were performed to examine doping thermal stability. Exposure of MoO3 and V2O5 transfer-doped hydrogen-terminated diamond samples up to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 31 publications
6
34
0
Order By: Relevance
“…Given that the surface area of the system was ~60Åx10Å this would mean that calculating the charge transfer per cm 2 would be ~6x10 13 cm -2 . This is comparable to reported experimental values obtained by hall measurements of MoO3 deposited on the surface of H-diamond substrates of ~2.5x10 13 -6x10 13 cm -2 carrier concentration [12]. Table 1 shows that the average electron population of the carbon atoms in the interfaced system decreased but, the average electron population of the hydrogen, molybdenum and oxygen atoms increased which is due to the charge transfer from the diamond through the hydrogen atoms to the MoO3.…”
Section: Simulation Methodologysupporting
confidence: 88%
“…Given that the surface area of the system was ~60Åx10Å this would mean that calculating the charge transfer per cm 2 would be ~6x10 13 cm -2 . This is comparable to reported experimental values obtained by hall measurements of MoO3 deposited on the surface of H-diamond substrates of ~2.5x10 13 -6x10 13 cm -2 carrier concentration [12]. Table 1 shows that the average electron population of the carbon atoms in the interfaced system decreased but, the average electron population of the hydrogen, molybdenum and oxygen atoms increased which is due to the charge transfer from the diamond through the hydrogen atoms to the MoO3.…”
Section: Simulation Methodologysupporting
confidence: 88%
“…Alongside the NEA, the corresponding high energy of the valence band allows surface transfer doping from adsorbates [10]. The deposition of a material with a large positive electron affinity onto the diamond surface can induce a twodimensional hole gas in diamond and has been used to develop diamond-based electronic devices such as capacitors and field effect transistors [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…'Transfer doping' of hydrogen-terminated diamond (H-diamond) presents a potential solution to this challenge which has allowed for the production of high performance FETs in terms of both high power [2] and high frequency operation [3]. Transfer doping of H-diamond has traditionally relied on the adventitious adsorption of air-borne electron-acceptor species onto the diamond surface when exposed to atmosphere however [4], and thus suffers from acute environmental and temperature sensitivity and associated instability [5]. Recent work by various groups has demonstrated significant advancements in the efficiency and stability of transfer-doped H-diamond by replacing the adsorbed surface atmospheric species with high electron affinity electron-acceptor oxide (EAO) materials such as MoO3…”
Section: Introductionmentioning
confidence: 99%
“…Though encouraging progress has recently been reported for FET devices that incorporate some of these EAO materials [11][12][13], the challenges associated with their integration into a diamond FET architecture and associated process flow have thus far limited their full potential to enhance both device performance and stability of operation. Furthermore, it was recently demonstrated that treatment of the H-diamond surface with a 400°C anneal prior to deposition of EAOs MoO3 and V2O5 is required to ensure stability of doping with time [5], thus placing additional thermal constraints on the processing required to integrate these materials into real devices. Although some work has already investigated the impact of exposure of more traditional H-diamond FET devices to temperatures up to 400°C e.g.…”
Section: Introductionmentioning
confidence: 99%